2022
DOI: 10.1111/geb.13551
|View full text |Cite
|
Sign up to set email alerts
|

Spatially explicit risk mapping reveals direct anthropogenic impacts on migratory birds

Abstract: Increasingly sophisticated modelling of satellite-derived data has transformed biodiversity monitoring and conservation (Hansen et al., 2013;Klein Goldewijk et al., 2011;Turner, 2014), allowing high-resolution mapping of anthropogenic impacts on the natural world. Studies often focus on evaluating spatial exposure of populations to individual threats (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 187 publications
0
13
0
Order By: Relevance
“…Among long‐distance migrants, where exposure to anthropogenic change may vary hugely between individuals and populations across the annual cycle, this approach has the potential to deliver significant advances in our understanding of spatiotemporal threat exposure, and in turn to inform the spatiotemporal targeting of conservation efforts. By linking individual movement patterns to spatial change variation at high temporal resolution, our approach revealed that accumulated change exposure in our study species was generally highest during their winter life stage, despite the areas occupied during this season having undergone relatively lower levels of anthropogenic change than other parts of the species range (Figure 3a–c; Buchan et al, 2022a). Our results highlight the complexity of spatial variation in change exposure within and between migratory flyways, demonstrating the critical role migratory route choice plays in shaping the potential risks faced by individuals across the annual cycle (Hewson et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Among long‐distance migrants, where exposure to anthropogenic change may vary hugely between individuals and populations across the annual cycle, this approach has the potential to deliver significant advances in our understanding of spatiotemporal threat exposure, and in turn to inform the spatiotemporal targeting of conservation efforts. By linking individual movement patterns to spatial change variation at high temporal resolution, our approach revealed that accumulated change exposure in our study species was generally highest during their winter life stage, despite the areas occupied during this season having undergone relatively lower levels of anthropogenic change than other parts of the species range (Figure 3a–c; Buchan et al, 2022a). Our results highlight the complexity of spatial variation in change exposure within and between migratory flyways, demonstrating the critical role migratory route choice plays in shaping the potential risks faced by individuals across the annual cycle (Hewson et al, 2016).…”
Section: Discussionmentioning
confidence: 87%
“…Detailed assessment of the sensitivity-which can variously be influenced by, for instance, degree of specialism, fragile interspecific reliance, morphological traits (Buchan et al, 2022b;Foden et al, 2013;Mason et al, 2019)-of the target species to each anthropogenic change layer will complement exposure metrics. Similarly, our approach does not capture the capacity for fine-scale behavioral adaptation to risks, such as micro-avoidance (Everaert, 2014;Plonczkier & Simms, 2012), nor the extent to which individuals are risk-naïve or -omniscient (Klaassen et al, 2006).…”
Section: Ta B L Ementioning
confidence: 99%
“…Increasing wildfire activity is one of many consequences of climate change, but we chose to discuss these threats separately due to their different pathways and effects on fitness. While hunting and trapping is a major threat to migrating birds globally, particularly in the East Asian-Australasian and Afro-Palearctic migration systems (Yong et al 2015, Khelifa et al 2017, Buchan et al 2022), we did not find sufficient evidence of nonlethal effects of hunting during migration to include it in this review. We only briefly address stressors that are a consequence of the removal of elements from the landscape (e.g., habitat loss and fragmentation), though the importance of these factors in bird population declines cannot be understated.…”
Section: Anthropogenic Threat Typesmentioning
confidence: 90%
“…We have a poor understanding of migratory connectivity for most species (Cohen et al 2018, Marra et al 2019), further hampered by the difficulty of tracking the full migrations of small birds in real time. To identify where and when bird populations are exposed to threats during migration, further research on migratory connectivity (Webster et al 2002, Cohen et al 2019) together with spatially explicit threat maps that cover entire migration corridors (Tulloch et al 2015, Bowler et al 2020, Buchan et al 2022) and extend upwards into the airspace (Davy et al 2017, Cohen et al 2022a) will prove invaluable. Incorporating a temporal component to create dynamic threat maps can more accurately capture the seasonal ebbs and flows in risk that birds experience as they move across continents (Runge et al 2016, Bauer et al 2019).…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…The abundance of many bird populations, especially of those with a migratory lifestyle has significantly decreased over the last decades (Rosenberg et al, 2019). A multitude of direct and indirect factors, such as predation by pets, collisions with buildings and habitat degradation, contribute to this decline (Buchan et al, 2022). An increasing threat to migratory species is the use of wind power (Marques et al, 2014), resulting in mortality (Loss et al, 2013).…”
Section: Introductionmentioning
confidence: 99%